Improving the endurance of management students with the help of alternative aerobic meansObjective of the study is to evaluate the effectiveness of various aerobic forms of physical activity in developing the endurance of students majoring in management. - Budarnikov A.A.; Gerasimov M.V.; Mironov A.O.; Solnyshkina Yu.O. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to evaluate the effectiveness of various aerobic forms of physical activity in developing the endurance of students majoring in management. Methods and structure of the study. The relationships between the load characteristics of aerobic motor activity and changes in endurance indicators were studied in 48 students aged 18.5±1.6 years, represented by groups engaged in athletics, hiking, cycling, and swimming. Results and conclusions. According to the developed training programs, the content of endurance development measures is focused on triggering mechanisms of adaptation to cyclic loads in uniform modes of functioning of the motor-cardiac sphere. The strength of the links between the use of alternative means of physical activity and the level of endurance development indicates the advisability of selectively using the content and technological components of physical activity in solving the tasks of physical education for students.